Learning together for groundwater management: A case of the Devnadi Basin, Nashik, Maharashtra, India - Vora, Shuchi (Ubiquity Press, Ltd., 2024)
This paper documents the process of co-learning spaces for transdisciplinary learning for participatory groundwater and ecosystem management across research-practice-community collectives in the Devnadi River Basin, Sinnar Block of Nashik District in Maharashtra, India. The Devnadi river supported a groundwater-dependent ecosystem, but now flows for less than four months in a year due to excessive groundwater depletion. A group model building workshop was designed to build a collective vision among experts and community members, create shared ownership and set the tone for transdisciplinarity in understanding groundwater management. This could be an additional tool in a Participatory Groundwater Management toolbox. This process involved surfacing values and mental models through participatory Causal Loop Diagram building. The actors included hydrologists, hydrogeologists, ecologists, agricultural value chain experts, and community leaders. In a process of answering questions participants were working towards combining diverse knowledge(s) and values into equitable and effective collective action to gain shared benefits from a complex, contested, and often poorly understood resource.